Characterization of electrically conductive bundles for electronic wearable - Toh, Maax Wei En (Nanyang Technological University, 2025)
Electronic wearables are an emerging area of engineering research, with much focus on developing new materials and techniques. However, limited attention has been given to the long-term performance of the conductive threads used in these wearables. This study evaluates the electrical stability of elastic bundles subjected to over 1 million cycles of testing, with varying levels of pre-stretch and strain to simulate real-world fabric stress. Both capacitance and resistance were measured to assess performance. Results indicate that while resistance fluctuated significantly, rendering it unsuitable for dynamic applications, capacitance remained relatively stable, supporting its suitability for capacitive touch sensing. These insights are crucial for optimizing future wearable designs